2019
DOI: 10.1007/s00221-019-05607-x
|View full text |Cite
|
Sign up to set email alerts
|

Is the manual following response an attempt to compensate for inferred self-motion?

Abstract: If the surrounding of a visual target unexpectedly starts to move during a fast goal-directed hand movement, the hand reflexively moves along with it. This is known as the ‘manual following response’. One explanation for this response is that it is a compensation for inferred self-motion in space. Previous studies have shown that background motion gives rise to both postural responses and deviations in goal-directed hand movements. To evaluate whether compensation for inferred self-motion is responsible for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…It is an automatic response that simply updates the planned endpoint of the movement to match the motion in the vicinity. It does not involve an explicit estimation of self-motion and is therefore compatible with the MFR being more prominent than postural responses to background motion ( Zhang et al, 2018 ) and to it not being found after illusory self-motion induced by vestibular stimulation ( Zhang et al, 2019 ), as well as with the finding that the presence of static structures does not influence the MFR. It can also explain the experimental characteristics of the MFR we report here: The preceding stability of the environment and the presence of static background structures are not considered.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…It is an automatic response that simply updates the planned endpoint of the movement to match the motion in the vicinity. It does not involve an explicit estimation of self-motion and is therefore compatible with the MFR being more prominent than postural responses to background motion ( Zhang et al, 2018 ) and to it not being found after illusory self-motion induced by vestibular stimulation ( Zhang et al, 2019 ), as well as with the finding that the presence of static structures does not influence the MFR. It can also explain the experimental characteristics of the MFR we report here: The preceding stability of the environment and the presence of static background structures are not considered.…”
Section: Discussionsupporting
confidence: 69%
“…The MFR describes the response of the hand in the direction of sudden background motion when the hand is moving to a target. Several experimental characteristics of the MFR have already been documented that are inconsistent with the idea that the mechanism underlying this response is an estimation of self-motion based on an instantaneous global optic flow analysis ( Zhang et al, 2019 ). Here, we find additional characteristics of the MFR that are also inconsistent with that idea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well documented that the moving arm quickly follows target displacements (reviewed by Smeets, Oostwoud Wijdenes, & Brenner, 2016 ). It is also known that the moving arm quickly follows motion onsets in the surrounding area (e.g., Brenner & Smeets, 1997 ; Gomi, Abekawa, & Nishida, 2006 ; Saijo, Murakami, Nishida, & Gomi, 2005 ; Whitney, Westwood, & Goodale, 2003 ; Zhang, Brenner, Duysens, Verschueren, & Smeets, 2018 , Zhang, Brenner, Duysens, Verschueren, & Smeets, 2019 ), in particular if they occur near the anticipated movement endpoint (e.g., Brenner & Smeets, 2015 ; Crowe, Smeets, & Brenner, 2021 ). We propose that this following response is due to shifting the planned movement endpoint in the direction of the motion onset (Crowe et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%